2023
DOI: 10.3390/metabo13050644
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Biomarkers in Late Preterm Neonates with Respiratory Distress Syndrome (RDS) Using Urinary Metabolomic Analysis

Abstract: Urine metabolomics is gaining traction as a means of identifying metabolic signatures associated with health and disease states. Thirty-one (31) late preterm (LP) neonates admitted to the neonatal intensive care unit (NICU) and 23 age-matched healthy LPs admitted to the maternity ward of a tertiary hospital were included in the study. Proton nuclear magnetic resonance (1H NMR) spectroscopy was employed for urine metabolomic analysis on the 1st and 3rd days of life of the neonates. The data were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Very few studies have applied metabolomics in preterm infants with RDS to investigate their metabolic profile and possibly identify metabolic alterations/pathways associated with the pathophysiology of RDS. In these studies, bronchoalveolar lavage fluid (BALF) [15,16] and urine were used as specimens [17]. In the present study, gastric fluid was the biofluid of interest, in which four amino acids were found to be significantly higher in infants treated with surfactant compared to controls.…”
Section: Biochemical Role and Origin Of Identified Metabolitesmentioning
confidence: 92%
“…Very few studies have applied metabolomics in preterm infants with RDS to investigate their metabolic profile and possibly identify metabolic alterations/pathways associated with the pathophysiology of RDS. In these studies, bronchoalveolar lavage fluid (BALF) [15,16] and urine were used as specimens [17]. In the present study, gastric fluid was the biofluid of interest, in which four amino acids were found to be significantly higher in infants treated with surfactant compared to controls.…”
Section: Biochemical Role and Origin Of Identified Metabolitesmentioning
confidence: 92%